1980
DOI: 10.1111/j.1365-2141.1980.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surgical Trauma on Human Granulopoiesis

Abstract: Marked changes in the concentration and proliferative state of circulating granulocytic progenitor cells (colony forming units in culture; CFUc) were observed in female patients following surgical trauma. Within one day of an abdominal hysterectomy there was an abrupt fall in the number of blood CFUc to between 10% and 20% of normal and an increase in the proportion synthesizing DNA which coincided with the maximum neutrophilia. Subsequently, as the neutrophil count declined, the CFUc concentration increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The fact that the highest levels of this enzyme occur in the youngest circulating cells (24) suggests that after hysterectomy the mobilization of reserve pools is followed by increased production and release of neutrophils from the bone marrow which begins to subside after 3 to 4 days. Previous measurements of granulocyte progenitor cells in the circulation after abdominal hysterectomy support this interpretation (20).…”
Section: Discussionmentioning
confidence: 81%
“…The fact that the highest levels of this enzyme occur in the youngest circulating cells (24) suggests that after hysterectomy the mobilization of reserve pools is followed by increased production and release of neutrophils from the bone marrow which begins to subside after 3 to 4 days. Previous measurements of granulocyte progenitor cells in the circulation after abdominal hysterectomy support this interpretation (20).…”
Section: Discussionmentioning
confidence: 81%
“…We did not analyze leukocyte counts 24 hours after surgery, a time point at which others have found a pronounced rise in neutrophils. 28 An experimental study from Gabka et al 29 showed that phagocytosis of 3 H-labeled Staphylococcus aureus was significantly lower in wound neutrophils from irradiated fields compared with controls at 6 and 12 weeks after radiation. The long-time interval between radiation and assay measurements eliminates the possibility that the neutrophils harvested were ever exposed to radiation themselves, given their short life span and the fact that they are rarely found in extravascular sites.…”
Section: Discussionmentioning
confidence: 97%
“…These areas are to some extent affected by RT to the pelvis, which results in depressed bone marrow. This might lead to preoperative leucopenia and an impairment of postoperative leucocytosis, which is normally seen within 24 hours after surgery 80 .…”
Section: Immunological Response To Treatmentmentioning
confidence: 99%